Mengurai diskresi administratif dan kriminslisasi kebijakan: kajian atas vonis tom lembong - ma'ruf, amar (Maliki Interdisciplinary Journal, 2026)
The conviction of Thomas Trikasih Lembong, former Minister of Trade, in a case involving alleged corruption in sugar import policy has revived the debate over the boundaries of administrative discretion and the potential criminalization of public policy. This article aims to outline the chronology of the case, analyze the legal considerations in the court’s decision, and examine the concept of administrative discretion based on Law Number 30 of 2014 on Government Administration. Furthermore, this paper discusses the application of mens rea elements in corruption offenses and offers reflections on the distinction between administrative policy and criminal acts. Through a juridical-normative approach and a literature review of reputable legal journals, the study finds that the criminalization of public policies carried out lawfully and within the scope of authority may hinder innovation and discourage officials from making strategic decisions. Therefore, clearer norms and strengthened understanding of good governance principles are needed to prevent discretion from being misinterpreted as an abuse of power.